2014
DOI: 10.3347/kjp.2014.52.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Hymenolepis nana Infection Possibly Through Organic Foods: Report of a Case

Abstract: We encountered a patient with heavy Hymenolepis nana infection. The patient was a 44-year-old Korean man who had suffered from chronic hepatitis (type B) for 15 years. A large number of H. nana adult worms were found during colonoscopy that was performed as a part of routine health screening. The parasites were scattered throughout the colon, as well as in the terminal ileum, although the patient was immunocompetent. Based on this study, colonoscopy may be helpful for diagnosis of asymptomatic H. nana infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Remarks: The recovered cestode parasite was compared with those collected from different regions: it most closely resembled H. nana previously described by Lapage (1951), Roberts & Janovy (2000), Schantz (2006), Richard (2008), Schmidt et al (2009), Sadaf et al (2013), and Kim et al (2014), since all of them had generic characteristics, except that reported by Mayhew (1925), which indicated that the testes were a compound structure. The parasite is also substantially similar to H. roudabushi due to the serrate strobila margins as described by Macy & Rausch (1946).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Remarks: The recovered cestode parasite was compared with those collected from different regions: it most closely resembled H. nana previously described by Lapage (1951), Roberts & Janovy (2000), Schantz (2006), Richard (2008), Schmidt et al (2009), Sadaf et al (2013), and Kim et al (2014), since all of them had generic characteristics, except that reported by Mayhew (1925), which indicated that the testes were a compound structure. The parasite is also substantially similar to H. roudabushi due to the serrate strobila margins as described by Macy & Rausch (1946).…”
Section: Resultssupporting
confidence: 64%
“…The evaginated juveniles were pushed out into the intestinal lumen after eosinophilic infiltration and possible physical pressure (days 4-5), where they matured into adult worms within 7 days (day 12). Prevalence and intensity: 20 out of 50 (40%) specimens were infected, with a total number of 243 cestodes Remarks: The recovered cestode parasite was compared with those collected from different regions: it most closely resembled H. nana previously described by Lapage (1951), Roberts & Janovy (2000), Schantz (2006), Richard (2008), Schmidt et al (2009), Sadaf et al (2013), and Kim et al (2014), since all of them had generic characteristics, except that reported by Mayhew (1925), which indicated that the testes were a compound structure. The parasite is also substantially similar to H. roudabushi due to the serrate strobila margins as described by Macy & Rausch (1946).…”
Section: Developmental Biology Of Cysticercoid and Adult H Nana In Micementioning
confidence: 79%
“…It implies to the poor sanitation because the soil was contaminated with parasite eggs from human waste or food supplies were contaminated with fleas, then eaten by human. As H. nana is one of a few parasites that can cause autoinfection and can persist for years, this also can be a potential problem to highly immunosuppressed hosts [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal parasitoses are one of the most important public health concerns, around one fifth of the world population is infected with at least one parasite (Puente et al, 2011). Hymenolepiosis by H. nana is mainly common in children, but H. diminuta infections have been also reported (Kim et al, 2014). Hymenolepiosis are usually asymptomatic, however, heavy infections with more than 2000 worms can induce a wide range of gastrointestinal symptoms, such as abdominal pain and diarrhea (Rim et al, 1978).…”
Section: Introductionmentioning
confidence: 99%